[en] JOÃO GOULART S OTHER HISTORIES: CHARACTER DEVELOPMENT ON BRAZIL S POLITICAL STAGE - ANNA LEE ROSA DE FREITAS (MAXWELL, 2007)
[pt] Umas histórias outras de João Goulart: a construção de um personagem no teatro da política brasileira é um ensaio - em que narração e descrição foram mescladas com a escrita argumentativa - sobre a trajetória enigmática do ex-presidente João Goulart, do Golpe de 64 até sua morte no exílio, em 1976. O palco político onde Jango atuou serve de objeto a esta dissertação não para investigar sua dimensão histórica, mas com o propósito de revelar e analisar criticamente a trama de discursos que tentaram desvendar essa trajetória, os quais estão instalados em estatutos diferentes. São eles: o fabulista, utilizado pelo cineasta Glauber Rocha, o memorialista, pelo antropólogo Darcy Ribeiro, o epistolar, pelo próprio Jango, o oficial, pelo governo da Ditadura Militar, o informativo, pela imprensa, e, ainda, o ficcional/jornalístico, pela autora da dissertação, que, ao incluir um texto com sua própria assinatura, no corpus textual da pesquisa, pretendeu evidenciar a orientação auto-identificadora e auto-reflexiva da mesma. A perspectiva teórica com a qual se trabalhou foi a de que os relatos do governo e da imprensa, enquanto propostas de verdade conclusiva, são apenas reativos e não correspondem ao poder que exerceram, na circunstância de sua divulgação. De acordo com essa visão, a força especulativa só existe na atividade fabuladora, isto é, só a arte e os discursos claramente interessados é que ativam os signos do passado, tornando-os passíveis de desvendamento, ao mesmo tempo em que se prestam a reflexões que servem para entender o presente. === [en] João Goulart s Other Histories: Character Development on Brazil s Political Stage is an essay - and as such its style is a combination of narration, description, and argumentative or academic prose - which chronicles the path of Brazilian former president João Goulart starting the 1964 coup until his death in exile in 1976. Jango s political setting, as well as the role he plays in it, serves here not as a means of assessing his historical standing, but rather as an object whose purpose is to unveil and critically scrutinize the discourse networks and webs elicited by the former president s political path. These discursive webs appear in a wide variety of categories: there is the storyteller s point of view as seen in the works of filmmaker Glauber Rocha; the anthropologist Darcy Ribeiro s memorialist take; Jango s own epistolary writings; the official version supported by the members of the dictatorial regime; the documental or journalistic disseminated by the media. Finally, in addition to these categories is the fictional/journalistic style adopted by the author of this dissertation as she opts to include an essay bearing her own signature into the corpus of her research. Her intent at doing so: locating and acknowledging her awareness of her stance vis a vis the subject at hand. The present research operates under one theoretical assumption: that official documents and press materials, far from being actual conclusive facts, are mainly reactive in nature. In other words, over the years they have lost their claim to truth. Subscribing to these views, this essay contends that speculation into the past is only achievable if combined with the ability to generate narratives, be these fictional or not. Only imbued with self-reflexive discourse and only within the sphere of art would one be able to activate signs of the past - thus rendering them not only intelligible but capable of eliciting reflection and of offering clues to understanding the present.